Effects of Soil Bulk Density on Gas Transport Parameters and Pore‐Network Properties across a Sandy Field Site. Issue 7 (10th July 2015) - Masís-Meléndez, Federico; de Jonge, Lis Wollesen; Chamindu Deepagoda, T. K. K.; Tuller, Markus; Moldrup, Per
Abstract : The gas diffusion coefficient, air permeability, and their interrelations with air‐filled porosity are essential for characterization of diffusive and convective transport of gases in soils. Variations in soil bulk density can affect water retention, air‐filled pore space, and pore‐network connectivity and tortuosity and, thereby, control gas diffusion and air permeability. Considering 86 undisturbed core samples with variable bulk densities that were extracted on a 15 by 15 m grid from the top layer of a sandy field, the effects of soil bulk density on gas transport parameters and the soil water characteristic were investigated. Interactions with soil organic matter, sand, and clay fractions were also examined. To evaluate bulk density effects, two constitutive parameters were derived from each of the three measured relationships. The Campbell pore‐size distribution index ( b ) and the air‐entry matric potential (ψae ) were derived from the soil water characteristic; the diffusive percolation threshold (εDPT ), the air‐filled porosity where gas diffusivity ceases to almost zero because of interconnected water films creating isolated–inactive air content, and a pore‐network connectivity index ( A 2 ) were derived from the gas diffusivity curve, and the analogous parameters convective percolation threshold (εCPT ) and convective pore‐network connectivity index ( B 2 ) from the air permeability curve. All six parameters showed significant negative correlations with bulk density. To further account for the effects of both bulk density and macroporosity in parametric gas transport models, a diffusive‐analog macroporosity–dependent model (DAMP) for gas diffusivity and a generalized Kawamoto et al. model (GK) for air permeability, which yielded improved predictive capabilities when compared with previous models, were developed. Both new models apply a reference point of prediction at −100 cm H2 O matric potential (macroporosity drained), corresponding to the point where analysis of pore‐network tortuosity (T) and equivalent pore diameter for gas transport ( d g ) showed diminishing effects of water blockage on gas transport in the sandy soil.